2011
DOI: 10.1111/j.1443-1661.2011.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Capsule Endoscopy Findings in Patients With Occult or Overt Bleeding Older Than 80 years

Abstract: WCE is feasible, although rather tiresome, in patients over the age of 80. Though the vast majority of patients older than 80 presented with angiodysplasias, there were no differences between the aged and younger groups in the presence of ulcerative lesions and polyps or tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 22 publications
2
20
3
Order By: Relevance
“…[19] However, this improved efficacy should be balanced by the worsening of the side effects of these explorations in elderly patients. [20] Moreover, no specific guidelines are available for patients aged over 65 years.…”
Section: Introductionmentioning
confidence: 99%
“…[19] However, this improved efficacy should be balanced by the worsening of the side effects of these explorations in elderly patients. [20] Moreover, no specific guidelines are available for patients aged over 65 years.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis reviewing the safety, tolerability, and findings of capsule endoscopy in the elderly found no significant differences in small bowel transit time or overall safety relative to a matched younger cohort. 88 However, the elderly participants were significantly more likely to label the procedure as tiresome and difficult. 88 The largest cohort study revealed that patients older than 80 were not more likely to suffer adverse events, defined as aspiration or capsule retention, compared with younger participants.…”
Section: Videocapsule Endoscopymentioning
confidence: 99%
“…88 However, the elderly participants were significantly more likely to label the procedure as tiresome and difficult. 88 The largest cohort study revealed that patients older than 80 were not more likely to suffer adverse events, defined as aspiration or capsule retention, compared with younger participants. 89 Further analysis showed capsule endoscopy to have a higher diagnostic yield in the over 80 population (73%) compared with the younger participants (55%) because of higher frequency of vascular lesions (angiodysplasia).…”
Section: Videocapsule Endoscopymentioning
confidence: 99%
“…There is scarcity of data on the use of CE in octogenarians. [2][3][4] We aim to report our centre experience in using CE in octogenarians. Methods Retrospective study; the SBCE data base of our unit was interrogated for patients >80 years of age who underwent CE.…”
mentioning
confidence: 99%